Epidemiology of patch tested patients with permanent tattoos—A comparative analysis of 9693 IVDK patients (2020–2022) - Schubert, S.; Oppel, E.; Bauer, A.; Schröder-Kraft, C.; Löffler, H.; Strom, K.; Worm, M.; Brans, R.; Wagner, Nicola; Angela, Y.; Geier, J.; Beiteke, Ulrike; et al. (Contact Dermatitis, 2024)
Background: Permanent tattooing is the invasive introduction of tattoo ink (pigments) into the dermis. The ink and aftercare cosmetics applied on pre-damaged skin may contain skin sensitisers. Objectives: To identify patient characteristics and the pattern of sensitisation in tattooed patients patch tested within the Information Network of Departments of Dermatology (IVDK). Patients and Methods: Comparative analysis of patient characteristics and reaction frequencies to baseline series allergens in 1648 consecutive patients with and 8045 consecutive patients without permanent tattoos. Non-overlapping 95%-confidence intervals were considered as significant. Results: Having permanent tattoos was related with female sex, age <40 years, tobacco smoking, atopic dermatitis, (occupational) hand dermatitis and being employed in particular occupational groups (e.g., healthcare workers, mechanics, hairdressers). Sensitisation to nickel was increased in tattooed patients and associated with female sex (OR 4.23 [95%-CI, 3.48–5.18]), age ≥40 years (OR 1.26 [95%-CI, 1.08–1.49]), tobacco smoking (OR 1.19 [95%-CI, 1.01–1.40]) and having permanent tattoos (OR 1.27 [95%-CI, 1.05–1.53]). Conclusions: The association between nickel sensitisation and permanent tattoos is probably confounded by past reactions to pierced costume jewellery. Socio-economic factors most probably contribute to the connection between tattoos, tobacco smoking, occupational or hand dermatitis, and being employed in particular occupational groups.
CRIS-Team Scopus Importer:2024-07-26
Keywords: allergic contact dermatitis; nickel; patch test; permanent make-up; tattoo; tattoo aftercare cosmetics